Debt maturity structure, institutional ownership and accounting conservatism - Mahdi Salehi; Mohsen Sehat (Asian Journal of Accounting Research, 2018)
The purpose of this paper is to examine the impact of debt maturity structure and types of institutional ownership on accounting conservatism by using different financial variables and proxies.Employing panel data analysis in the R programming language, the authors test their hypotheses on a sample of 143 (858 firm-year observations) companies listed on the Tehran Stock Exchange during 2011–2016.Using Basu (1997) and Beaver and Ryan (2000) models as proxies for accounting conservatism, the findings suggest a non-significant relationship between accounting conservatism and debt maturity structure. Contrary to the primary expectation, the results indicate that short-maturity debts are also non-significantly and negatively associated with accounting conservatism in financially distressed firms. Finally, using both conservatism measures, the authors document that there is no significant relationship between both active and passive institutional ownership and accounting conservatism as well as debt maturity structure.The current study is the first study conducted in a developing country like Iran, and the outcomes of the study may be helpful to other developing nations.